2018
DOI: 10.3390/nu10081086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioelectrical Impedance Analysis, Slaughter Skinfold-Thickness Equations, and Dual-Energy X-ray Absorptiometry for Estimating Body Fat Percentage in Colombian Children and Adolescents with Excess of Adiposity

Abstract: Dual-energy X-ray absorptiometry (DXA) has been considered a reference method for measuring body fat percentage (BF%) in children and adolescents with an excess of adiposity. However, given that the DXA technique is impractical for routine field use, there is a need to investigate other methods that can accurately determine BF%. We studied the accuracy of bioelectrical impedance analysis (BIA) technology, including foot-to-foot and hand-to-foot impedance, and Slaughter skinfold-thickness equations in the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 60 publications
3
27
1
7
Order By: Relevance
“…BFP bias was approximately −0.5% in boys and approximately −4.7% in girls using the Slg‐Eq method. A similar tendency was observed by González‐Ruiz et al , who found that Slg‐Eq underestimated BFP by 9.0% in boys and 11.1% in girls. We did not find significant differences by sex using BIA, but our data seemed to show a slightly opposite tendency than González‐Ruiz et al found, in which mean bias was larger in boys (14.0%) than in girls (11.0%).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…BFP bias was approximately −0.5% in boys and approximately −4.7% in girls using the Slg‐Eq method. A similar tendency was observed by González‐Ruiz et al , who found that Slg‐Eq underestimated BFP by 9.0% in boys and 11.1% in girls. We did not find significant differences by sex using BIA, but our data seemed to show a slightly opposite tendency than González‐Ruiz et al found, in which mean bias was larger in boys (14.0%) than in girls (11.0%).…”
Section: Discussionsupporting
confidence: 87%
“…Noradilah et al included, however, a complete range of weight status (i.e., from severely thin to obesity), which might also explain the higher variability between measurements. This idea has also been reported in the recent study by González‐Ruiz et al in children and adolescents (11‐17 years) with excess adiposity. They also found that BIA and Slg‐Eq underestimated BFP compared with DXA and that the differences in Slg‐Eq against DXA could be related to the larger SKF thickness, as Slaugther et al included a sample with lower adiposity to develop their equations.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Second, we did not measure specific cognitive outcomes that underlie executive function and physical activity. Similarly, the lack of gold‐standard measurements of adiposity (ie, Bod Pod and dual‐energy X‐ray absorptiometry) should be acknowledged as another limitation 35. A strength of the present study lies in the fact that it is the first study, to our knowledge, to assess the relationship between physical fitness and attention among Latin American youth population.…”
Section: Discussionmentioning
confidence: 92%